2018
DOI: 10.1016/j.memsci.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liquid transport properties of hydrophobic polymers of intrinsic microporosity by electrical resistance measurement

Abstract: In this work, the electrical resistance method was used to get an insight of the liquid transport through the polymers with excess of fractional free volume. The dense films based on the first generation of polymers of intrinsic microporosity, disubstituted polyacetylenes PMP and PTMSP, were used; water-ethanol binary mixtures allowed to adjust the affinity of the liquid phase to selected polymers continuously. In this work, the liquid-membrane interaction was considered as a stepwise occupation of accessible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The critical conductor fraction was determined by the Monte Carlo methods (Kirkpatrick, 1973;Vysotskii et al, 1995;McLachalan et al, 1993;Hsu et al, 1980), and it was found that this value is related to the size and the orientation of particles of both phases, and for three-dimensional systems. However, in experiments with a strong asymmetry of the conducting and non-conducting forms, the values can be even larger (Kirkpatrick, 1973;Hsu and Berzins, 1985;Yushkin et al, 2018). Thus, the values obtained agree with the literature data.…”
Section: Figure 9 Dependence Of the Electrical Conductivity Of The Membrane On (A) The Alcohol Concentration And (B) The Membrane Porositsupporting
confidence: 89%
See 3 more Smart Citations
“…The critical conductor fraction was determined by the Monte Carlo methods (Kirkpatrick, 1973;Vysotskii et al, 1995;McLachalan et al, 1993;Hsu et al, 1980), and it was found that this value is related to the size and the orientation of particles of both phases, and for three-dimensional systems. However, in experiments with a strong asymmetry of the conducting and non-conducting forms, the values can be even larger (Kirkpatrick, 1973;Hsu and Berzins, 1985;Yushkin et al, 2018). Thus, the values obtained agree with the literature data.…”
Section: Figure 9 Dependence Of the Electrical Conductivity Of The Membrane On (A) The Alcohol Concentration And (B) The Membrane Porositsupporting
confidence: 89%
“…This created the observed hysteresis. It should also be noted that previously hysteresis phenomena were observed in various polymers with internal microporosity (Yushkin et al, 2018), and in hydrophilic cellophane .…”
Section: Figure 9 Dependence Of the Electrical Conductivity Of The Membrane On (A) The Alcohol Concentration And (B) The Membrane Porositmentioning
confidence: 61%
See 2 more Smart Citations
“…1). The effects of "fractional free volume" in rigid microporous polymer structures on ion transport and conductivity have been considered [34]. In PIM-EA-TB, there are "free volume elements" providing multiple amine site, which after protonation allow anion binding into "cavities".…”
Section: mentioning
confidence: 99%